Deriving values of the social rate of time preference - Chris Parker (New Zealand Government, The Treasury, 2025)
This report estimates the "social rate of time preference" (SRTP) for New Zealand public policy appraisal using a Ramsey equation. It uses the Weitzman (1998) method to derive a declining discount rate schedule of 2% (real) for years 1-30, 1.5% for years 31-100, and 1% for years 101 on. The report does not compare and contrast social discount rate methods and how to use them in practice.
Keywords: H43; H50; 330; Discounting; social discount rate; time preference; Government